Nanopillar films with polyoxometalate-doped polyaniline for electrochemical detection of hydrogen peroxide. Issue 4 (14th January 2016) - Yang, MinHo; Kim, Dong Seok; Yoon, Jo Hee; Hong, Seok Bok; Jeong, Soon Woo; Yoo, Dong Eun; Lee, Tae Jae; Lee, Seok Jae; Lee, Kyoung G.; Choi, Bong Gill
Abstract : An enzymeless electrochemical sensor was developed for detection of hydrogen peroxide based on the use of highly ordered polyoxometalate-doped polyaniline nanopillar arrays. Abstract : Design and fabrication of electrodes is key in the development of electrochemical sensors with superior electrochemical performances. Herein, an enzymeless electrochemical sensor is developed for detection of hydrogen peroxide based on the use of highly ordered polyoxometalate (POM)-doped polyaniline (PANI) nanopillar films. The electrodeposition technique enables the entrapment of POMs into PANI during electropolymerization to produce thin coatings of POM-PANI. Electrochemical investigations of the POM-PANI/nanopillar electrode showed well-defined multiple pairs of redox peaks and rapid electron transfer. The nanopillar structure facilitated the diffusion of the electrolyte and thus, enhanced the redox reaction. In particular, the POM-PANI/nanopillar electrode was incorporated into a flow injection biosensor and it demonstrates its electrocatalytic activity to detect hydrogen peroxide with high sensitivity, rapid response time, and low detection limit.